IDENTIFIKASI PENYEDIA JASA KONSTRUKSI SEBAGAI APLIKATOR BUILDING INFORMATION MODELLING DI INDONESIA (Identify construction service providers as Building Information Modeling applicators in Indonesia) - Bambang Herumanta; Agus Nugroho (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
The Indonesian government through the Minister of Public Works and Public Housing Regulation number 22/2018 has required the use of BIM in the construction of state buildings with criteria above 2000 square meters and over two floors. These regulations are binding on stakeholders such as owners, consultants, and contractors. This study aims to identify construction service business entities related to the use of Digital Building Information Modeling technology. The research steps included: preparing the object of research in the form of a list of contractors and consultants in Indonesia. The various data collection methods used to find and complete the data required in this research process were: preparation of data search tools in the form of questionnaires, interviews with contractors and consultants, Submitting questionnaires to contractors and consultants. Processing and analysis of the data that has been obtained is then processed and analyzed for the preparation of the final research report. Data processing was carried out using statistical software tools. The results showed that the companies that implemented BIM the longest, namely> 5 years were 28%, the 1-2 years time span was 17%, the 3-4 years time span was 22%, and those <1 years were 33%. Companies that apply BIM> 5 years according to our data are state-owned companies (State-Owned Enterprises), while those with less than one year of experience are private companies. Reduction of time for contractors and / or consultants, for KW10-15 by 17%, KW15-30 by 17%, KW30-40 by 22%, and for K40-50 by 44%. In terms of time, the effect of implementing BIM in companies can be said to reduce the amount of time and the most dominant is the reduction of time by 40% - 50%. Cost reduction for contractors and / or consulting companies, for KB5-15 by 50%, KB15-25 by 16%, KB25-30 by 17%, and for KB30-40 by 17%. In terms of costs, as a result of implementing BIM in companies, it can be said that it reduces the amount of costs and the most dominant is the cost reduction of between 5% - 15%.